Determination of growth regimes of Pt nanostructures on GaN (0001) based on the control of Pt thickness and annealing time: Morphological evolution of Pt nanostructures from the nanoparticles, nanoclusters to porous network. (May 2019) - Pandey, Puran; Sui, Mao; Kunwar, Sundar; Li, Ming-Yu; Zhang, Quanzhen; Lee, Jihoon
Pt nanostructures are applicable in various applications such as sensors, solar cells, light emitting devices and catalysis and only slight changes in their configuration, density and size can induce significant changes in their properties and thus the functionality in the related applications. In this paper, the systematical evolution of Pt nanostructures such as nanoparticles, nanoclusters and porous network on GaN (0001) is demonstrated by the systematic thermal annealing of Pt thin films based on the combinational effects such as thermal dewetting, Volmer-Weber growth model and coalescence growth. In particular, small dome-shaped self-assembled Pt nanoparticles with relatively smaller deposition amount (<2 nm) and wiggly Pt nanoclusters between 3 and 5 nm are formed based on the Volmer-Weber growth model and the partial coalescence of Pt nanoparticles, respectively. Between 10 and 30 nm, the growth of Pt nanoclusters is observed and eventually with the increased Pt thickness range between 40 and 100 nm, nanoclusters gradually develop into the porous Pt network by connecting neighboring structures owing to the enhanced coalescence growth. Meanwhile, along with the annealing time variation between 0 and 3600 s, the rate of dewetting is increased and as a result, the evolution of densely packed to separated nanoclusters is formed. In addition, the optical properties of corresponding Pt nanostructures demonstrate that the photoluminescence and Raman intensity are reduced along with the evolution of the surface coverage of Pt nanostructures, whereas the average reflectance is significantly enhanced accordingly at the same time.